Emotional dysregulation features and problem gambling in university students: a pilot study. Issue 4 (4th August 2020) - Torrado, Marco; Bacelar-Nicolau, Leonor; Skryabin, Valentin; Teixeira, Mariana; Eusébio, Susana; Ouakinin, Silvia
Abstract: Undergraduate students typically cope with various changes in their lives and experience many stressors associated with academic issues. Distress can make them more vulnerable to particular behavioral patterns in order to cope with negative affect. The association of problematic gambling with particular emotion regulation characteristics—some of which are developmentally dependent—becomes a recent focus of research with clinical and preventive implications. We carried out a pilot study enrolling voluntarily young adults of a public university in the Lisbon area, and 117 Portuguese-speaking individuals were interviewed. Participants, mainly female ( M  = 20.6; SD = 3.9), were investigated taking into consideration their gambling practices, characteristics of impulsivity and alexithymia, along with the symptoms of depression and anxiety. Portuguese versions of the South Oaks Gambling Scale (SOGS) and Short-Version of Impulsive Behavior Scale (S-UPPSP) were prepared (i.e., translation and back-translation of the original versions were performed). The prevalence of gambling problems in this sample is modest, although they were associated with negative urgency and sensation-seeking, as well as with depression symptoms. Multiple correspondence analysis, a particular multivariate model associating gambling problems with socio-demographic and psychological variables, allowed identifying different profiles of individuals. Trace and state emotional dysregulation features are selectively associated with distinctive gambling patterns, according to some previous findings in studies with other groups. Results may address new findings in terms of morbidity, risk factors and the design of future preventive strategies among such individuals.